Basic electronic component and circuits - Siti Fatimah Siraj; $a Norhayati Soin; Wan Nor Liza Wan Mahadi (Penerbit Universiti Malaysia Perlis, 2013)
This book provides a concise, practical guidance to understand and relate concepts and principles of electronics to analyze and solve electronic circuits